Traumatic perineal injury in a 13-year-old female: Case report and review of the literature - Dimitrios Godosis; Christos Kaselas; Charikleia Demiri; Kleanthis Anastasiadis; Theodora Tsiaprazi; Ioannis Spyridakis (MDPI AG, 2019)
Traumatic perineal injury in children is a rather underestimated condition, in terms of occurrence. The rapid stretching of the soft perineal environment, combined with the surrounding osseous tissue of the pelvis, can cause severe injuries. The key to successful management of these injuries includes timely resuscitation, thorough physical examination and quick and safe repair of damages.